Clinical features and septic screen in neonatal sepsis in a teaching hospital in India - Vijayan, Soja; Nair, Gopalan A. Velayudhan; Narayanan, Dhanya (International Journal of Contemporary Pediatrics, 2019)
Background: Sepsis remains a leading cause of mortality and morbidity, especially during the first five days of life and in low and middle-income countries. The purpose of this study was to note the clinical features and analyze the relationship between the septic screen and blood culture positive sepsis in the neonatal unit. Methods: A one-year descriptive cross-sectional study was carried out at the NICU of a teaching hospital in India. Results: The incidence of clinically suspected septicemia was 19.3 per 1000 live births and the incidence of blood culture positive septicemia was 2.9 per 1000 live births among the inborn of the hospital. The most common clinical features were poor suck and lethargy in culture positive sepsis. The most common organisms causing sepsis were Coagulase negative staphylococci and Klebsiella. In the septic screen CRP was found to have a statistically significant association with blood culture positive sepsis. CRP also had the highest sensitivity and negative predictive value among the studied parameters. Conclusions: Incidence of blood culture positive sepsis was 2.9 per 1000 live births among the inborn of the hospital. The most common clinical features were poor suck and lethargy in culture positive sepsis. The most common organism isolated in neonatal sepsis in the NICU was Coagulase negative staphylococcus. In resource poor settings, CRP continues to be an important tool in diagnosis and treatment of neonatal sepsis.